Study of Socio-Pedagogical Determinants in Programme for International Student Assessment - Matkarimov Akramjon Muxtorovich (Zien Journals, 2025)
This article examines the pedagogical aspects of forming and developing the learning environment within the family. Drawing on an analysis of the scientific literature, it explores the pedagogical dimensions, content, forms, and specific features of nurturing an educational environment at home. The development of such an environment is, first and foremost, characterized by parents’ positive attitudes toward education. As a result, education in the family becomes established as a “family value.” The article also offers recommendations aimed at fostering children’s motivation and positive attitudes toward learning in the family setting
Keywords: family; educational environment in the family; learning; favorable learning environment